2020
DOI: 10.1101/2020.02.05.936443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic control of visually-guided locomotion through cortico-subthalamic projections

Abstract: Goal-directed locomotion necessitates control signals that propagate from higher-order areas to regulate spinal mechanisms. The cortico-subthalamic hyperdirect pathway offers a short route for cortical information to reach locomotor centers in the brainstem. We developed a task where head-fixed mice run to a visual landmark, then stop and wait to collect reward, and examined the role of secondary motor cortex (M2) projections to the subthalamic nucleus (STN) in controlling locomotion. Our modeled behavioral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
(137 reference statements)
3
5
0
Order By: Relevance
“…Though in acute dopaminedepleted mice, repetitive PV + neuron stimulation was shown to persistently restore mobility [46], we did not observe a persistent behavioral effect in our chronic lesion model of PD. Consistent with the fact that STN 425 neuron activity is associated with movement inhibition [35,[100][101][102][103] 122], here, we showed that phasic inhibition of STN neurons is movement-promoting. In addition, as the GABAergic projection from PV + neurons to the SNr is also movement-promoting, this PV + -SNr projection further reinforces the movement promotion imposed by the PV + -STN projection.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Though in acute dopaminedepleted mice, repetitive PV + neuron stimulation was shown to persistently restore mobility [46], we did not observe a persistent behavioral effect in our chronic lesion model of PD. Consistent with the fact that STN 425 neuron activity is associated with movement inhibition [35,[100][101][102][103] 122], here, we showed that phasic inhibition of STN neurons is movement-promoting. In addition, as the GABAergic projection from PV + neurons to the SNr is also movement-promoting, this PV + -SNr projection further reinforces the movement promotion imposed by the PV + -STN projection.…”
supporting
confidence: 91%
“…In agreement with the established relationship between STN activity and movement suppression [35, [100][101][102][103], both direct recordings and theoretical models assert that the hypokinetic symptoms of PD are a result of excessive STN activity [6,15,[104][105][106][107][108][109][110][111]. Importantly, lesioning and inactivation studies from animal models of PD further support this idea [112,113] but see [114].…”
Section: Stimulation Of Pv + Neurons Lessens Hypokinetic Symptoms 390supporting
confidence: 59%
“…In agreement with the established relationship between STN activity and movement suppression (Hamani et al, 2004;Aron and Poldrack, 2006;Aron et al, 2007;Eagle et al, 2008;Schmidt et al, 2013;Schweizer et al, 2014;Fife et al, 2017;Wessel and Aron, 2017;Adam et al, 2020), both direct recordings and theoretical models assert that the hypokinetic symptoms of PD are a result of excessive STN activity (Albin et al, 1989;Bergman et al, 1994;Wichmann and DeLong, 1996;Bergman et al, 1998;Obeso et al, 2000;DeLong and Wichmann, 2007;Zaidel et al, 2009;Sharott et al, 2014;DeLong and Wichmann, 2015;McGregor and Nelson, 2019). Importantly, lesioning and inactivation studies from animal models of PD further support this idea (Levy et al, 2001;Yoon et al, 2014), but see (McIver et al, 2019).…”
Section: Stimulation Of Pv + Neurons Lessens Hypokinetic Symptomsmentioning
confidence: 58%
“…On the other hand, it is clear that the inhibitory projection to the STN (and substantial pars reticulata) mediates the motor-promoting effects, and it is consistent with the established relationship between STN activity and movement suppression (Hamani et al, 2004; Aron and Poldrack, 2006; Aron et al, 2007; Eagle et al, 2008; Schmidt et al, 2013; Schweizer et al, 2014; Fife et al, 2017; Wessel and Aron, 2017). In addition to the established literature demonstrating that the GPe sends inhibitory signals to the input and output nuclei of the basal ganglia (Jessell et al, 1978; Mink, 1996; Smith et al, 1998; Kita, 2007; Hegeman et al, 2016; Adam et al, 2020), recent studies highlight the existence of cortico-pallido-cortical loops (Naito and Kita, 1994; Chen et al, 2015; Saunders et al, 2015; Schwarz et al, 2015; Ahrlund-Richter et al, 2019; Karube et al, 2019; Abecassis et al, 2020; Adkins et al, 2020; Anastasiades et al, 2020; Clayton et al, 2020; Gehrlach et al, 2020; Lee et al, 2020; Muñoz-Castañeda et al, 2020; Garcia et al, 2021). However, the precise circuitry has yet to be defined.…”
Section: Discussionmentioning
confidence: 97%